Nitrate and Escherichia coli NAR analysis in tile drain effluent from a mixed tree intercrop and monocrop system - Dougherty, Michael C.; Thevathasan, Naresh V.; Gordon, Andrew M.; Lee, Hung; Kort, John (Agriculture, ecosystems & environment, 2009)
Contamination of groundwater in agricultural areas by nitrate and Escherichia coli can potentially lead to several harmful health effects for those who consume or are exposed to it. The objective of this study was to determine if trees can reduce loadings of these contaminants to the groundwater. Tile drain effluent from two adjacent agricultural systems (a mixed tree intercrop and a monocrop) was collected from April to November during 2005 and 2006 from a mini watershed area of 17,200 m 2. An area of 1100 m 2 (6.4%) in each system was subject to application of a mixture of water and a biotracer E. coli NAR, a naturally occurring strain that is resistant to naladixic acid and has been shown to be safe for introduction into the environment. The effluent was analyzed for concentrations of the biotracer and NO 3 −-N. The premise of this study is to determine if the safety-net hypothesis is valid in a temperate intercropping system. This hypothesis states that the incorporation of trees into agricultural systems will allow for a more efficient use of resources, since the rooting system of the trees capture nutrients that are not captured by the crop component of the system. The quantities of NO 3 −-N in the leachate were similar in 2005: 57.37 and 54.74 kg ha −1 leached from the monocrop and intercrop sites, respectively. However, in 2006, NO 3 −-N levels were significantly higher ( p < 0.05) in the monocrop effluent: 164.67 kg ha −1 compared to that of the intercrop, 88.59 kg ha −1. Few significant differences were found in E. coli NAR outputs during both years: for the same number of samples collected, the total colony forming units (CFUs) found in the monocrop and intercrop effluents, respectively were 4040 and 3558 in 2005 and 34,025 and 28,401 in 2006. This indicates that intercropping systems and perhaps trees in general have a potential mitigating effect on E. coli movement to the groundwater.